2022
DOI: 10.3390/nano12183153
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Transformation Induced Core–Shell Ni2P@Fe2P Heterostructures toward Efficient Electrocatalytic Oxygen Evolution

Abstract: The oxygen evolution reaction (OER) is a crucial reaction in water splitting, metal–air batteries, and other electrochemical conversion technologies. Rationally designed catalysts with rich active sites and high intrinsic activity have been considered as a hopeful strategy to address the sluggish kinetics for OER. However, constructing such active sites in non-noble catalysts still faces grand challenges. To this end, we fabricate a Ni2P@Fe2P core–shell structure with outperforming performance toward OER via c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…2b). The Fe 2+ peak at 710.77 eV is shifted positively referring to the binding energy of pristine Fe 2 P in the literature, 65,66 confirming that the electrons transfer from Fe to Co atoms at the heterogeneous interface of CoP/Fe 2 P. These observations indicate the strong electronic interaction between CoP and Fe 2 P. 41 After Cr incorporation, the characteristic peaks in Cr-CoP/Fe 2 P are also shifted. The two Co 3+ peaks in Cr-CoP/Fe 2 P obviously shift towards lower binding energy in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…2b). The Fe 2+ peak at 710.77 eV is shifted positively referring to the binding energy of pristine Fe 2 P in the literature, 65,66 confirming that the electrons transfer from Fe to Co atoms at the heterogeneous interface of CoP/Fe 2 P. These observations indicate the strong electronic interaction between CoP and Fe 2 P. 41 After Cr incorporation, the characteristic peaks in Cr-CoP/Fe 2 P are also shifted. The two Co 3+ peaks in Cr-CoP/Fe 2 P obviously shift towards lower binding energy in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…The obtained high-pore nitrogen-doped graphitized structure has good conductivity and structural stability. Combining with the effect between Fe and Ni, FeNiP/NC exhibits excellent OER activity and durability with an overpotential of only 240 mV at 10 mA/cm 2 and can be sustainable electrolyzed for 45 h. Density function theory (DFT) calculation proves that NC adjusted the adsorption strength of the intermediates and reduced the activation energy of the formation of *OH, *O, and *OOH. XRD, SEM, EDX, and XPS characterization after the stability test proved that FeNiP was converted into MOOH during electrolysis as the new catalytic active site.…”
Section: Introductionmentioning
confidence: 99%
“…41 Shao and co-workers prepared a Ni 2 P@Fe 2 P nanosheet using a Ni–MOF as a precursor, which exhibits an excellent OER performance with a low overpotential of 238 mV to drive 50 mA cm −2 in a KOH solution. 42 Although great progress has been made in the study of porous/hollow metal composite phosphides driven by MOFs, the current strategy for the preparation of metal composite phosphides is to prepare bimetallic MOF materials at first, and then to carry out phosphating, most of which are bimetallic phosphating. However, it is rarely reported that metal composite phosphating materials are obtained from a single MOF material.…”
Section: Introductionmentioning
confidence: 99%